MODAL MANUSIA ANGGOTA KELOMPOK TANI DALAM KEGIATAN USAHATANI JAGUNG DI DESA WAKADIA KECAMATAN WATOPUTE KABUPATEN MUNA - Viorera, Multi; Batoa, Hartina; Abdullah, Sukmawati (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
The evolution of corn farming in Wakadia Village, Watopute District, Muna Regency, which exhibits considerable promise in enhancing food security and regional economic vitality, is predominantly influenced by the caliber of farmers' human capital. This encompasses their knowledge, skills, education, and aptitude for technological adoption. Current levels of human capital development in this domain are deemed inadequate, underscoring the necessity for targeted and sustainable capacity-building initiatives. The objective of this study is to ascertain the human capital of farmer groups engaged in corn farming activities in Wakadia Village, Watopute District, Muna Regency. The research population consists of all corn farmers who are members of seven farmer groups in Wakadia Village, with a total of 196 people. The research sample consists of 66 people. The sampling technique employed was proportional random sampling. The research variables were human capital and corn farming activities. Quantitative descriptive methods were used to conduct the data analysis. The findings indicated that the corn farmer group members exhibited a predominantly moderate to good level of human capital, particularly with regard to their knowledge and skills in carrying out corn farming activities. The farmers' comprehensive understanding of the cultivation process, from land preparation to harvesting and post-harvesting, along with the technical skills acquired through farming experience and interaction within farmer groups, were found to be pivotal in fostering the sustainability of corn farming in Wakadia Village. However, the formal education of farmers remains comparatively limited, thereby impeding the enhancement of human capital capacity in a sustainable manner, particularly with regard to the implementation of agricultural innovations and technologies. Despite the evident success of corn farming activities, enhancing the human capital of farmers through educational initiatives, training programs, and ongoing support is imperative. This will empower farmer group members to optimize all stages of corn farming, increase productivity, and promote the sustainable well-being of farmers.